Pengaruh Rencana dan Realisasi Penggunaan Dana Bos Terhadap Kinerja Keuangan di SMA Al-Islam Krian Sidoarjo - Indah Sulistyowati; Darno Darno (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
BOS funds are costs allocated by the government specifically to support education in Indonesia. This study aims to examine the effect of BOS budget planning and the realization of the use of BOS funds on financial performance at Al-Islam Krian Sidoarjo High School. The variables used in this study are the BOS budget budget plan and the realization of the use of BOS funds which act as independent variables, as well as financial performance which acts as the dependent variable. The author uses descriptive quantitative methods in this study. The data collection technique carried out in this study was to use primary data obtained directly from the objects studied, namely by distributing questionnaires. The population in this study is the financial report of BOS Al-Islam Krian Sidoarjo High School in 2016-2018. The samples in this study were educators, education staff, and guardians of students who were involved in the BOS management team for the period of 2016 - 2018, with respondents totaling 35 people. The results of the study using multiple linear regression analysis based on the t test can be concluded that BOS budget planning has a significant and positive effect on financial performance and the realization of the use of BOS funds also has a positive and significant effect on financial performance.